Organically Modified Silica Nanoparticles with Intraparticle Heavy-Atom Effect on the Encapsulated Photosensitizer for Enhanced Efficacy of Photodynamic Therapy - Kim, Sehoon; Ohulchanskyy, Tymish Y.; Bharali, Dhruba; Chen, Yihui; Pandey, Ravindra K.; Prasad, Paras N. (American Chemical Society, 2009)
We report a novel nanoassembly formulation for photodynamic therapy, which is composed of covalently iodine-concentrated organically modified silica (ORMOSIL) nanoparticles (diameter < 30 nm) and a hydrophobic photosensitizer embedded therein. Comparative studies with iodinated and noniodinated nanoparticles have demonstrated that the intraparticle external heavy-atom effect on the encapsulated photosensitizer molecules significantly enhances the efficiency Of O-1(2) generation and, thereby, the in vitro PDT efficacy.
Keywords: DRUG